Early repolarisation among athletes - Claessen, Femke M A P (BMJ Open Sport Exerc Med, 2020)
OBJECTIVES: Traditionally, early repolarisation (ER) is considered a benign ECG variant, predominantly found in youths and athletes. However, a limited number of studies have reported an association between ER and the incidental occurrence of ventricular fibrillation or sudden cardiac death. Yet definite, direct comparisons of the incidence of ER in unselected, contemporary populations in athletes as compared with non-athletes and across different sports are lacking. This study therefore aimed to investigate whether ER is more common among athletes as compared with non-athletes, and if ER patterns differ between sport disciplines based on static and dynamic intensity. METHODS: To assess ER we retrospectively analysed ECGs of 2241 adult subjects (2090 athletes, 151 non-athletes), who had a sports medical screening between 2010 and 2014 in an outpatient clinic. The outcome was tested for confounders in a multivariable logistic regression analysis. RESULTS: ER was found in 502 athletes (24%). We found a 50% higher prevalence of ER in the athlete group compared with the control group (OR 1.5 (SE 0.34), adjusted 95% CI 1.0 to 2.4) in multivariable analysis. A 30% higher prevalence of ER in the inferior leads only (OR 1.3 (SE 0.38), adjusted 95% CI 0.74 to 2.3), a 120% higher prevalence of ER in the lateral leads only (OR 2.2 (SE 1.0), adjusted 95% CI 0.87 to 5.4), and a 20% higher prevalence of ER in the inferior and lateral leads (OR 1.2 (SE 0.49), adjusted 95% CI 0.55 to 2.7) was found in athletes. CONCLUSION: Athletes had a 50% higher prevalence of ER and a 30% higher prevalence of ER in the inferior leads specifically. There was no association between training duration or sports discipline and ER.